Traditional game box (TGB) - Wan Hassan, Wan Norhasmira; Muhammad Pozi, Muhamad Asyrafi; Mohd Faisal, Muhamad Amirudin; Che Darus, Mohd Dzairil Azhar; Selamat, Nordibradini (Universiti Teknologi MARA, Kedah, 2018)
Traditional Games Box (TGB) for kids is an educational tool that been developed to acknowledge youngster generation about our traditional games. It is also use to communicate and creating interactive learning between parents and their kids.